2022
DOI: 10.1155/2022/6755436
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anthropometric Indices with Menstrual Abnormality among Nursing Students of Nepal: A Cross-Sectional Study

Abstract: Introduction. Obesity has been reported to be linked with menstrual abnormalities including abnormality in cycle length, duration, and period blood loss. However, which anthropometric parameter is a better marker of menstrual abnormality is yet unknown. This study aims to explore the association of BMI, waist-hip ratio (WHR), and waist-height ratio (WHtR) with menstrual abnormalities. Methods. This was a cross-sectional study conducted among 240 nursing students on two nursing campuses of Nepal. Demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A higher waist and hip circumference were observed among the PCOS females than their non-PCOS females, WHr appeared to be significantly higher among the PCOS group 18 . Increased WHr was associated with periodic blood loss only whereas increased Waist-to-height ratio was associated with abnormal cycle length and period duration, but not menstrual blood loss 25 . In our study, both BMI and WHr were significantly high among individuals with the menstrual disorder than those without the disorder.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A higher waist and hip circumference were observed among the PCOS females than their non-PCOS females, WHr appeared to be significantly higher among the PCOS group 18 . Increased WHr was associated with periodic blood loss only whereas increased Waist-to-height ratio was associated with abnormal cycle length and period duration, but not menstrual blood loss 25 . In our study, both BMI and WHr were significantly high among individuals with the menstrual disorder than those without the disorder.…”
Section: Discussionmentioning
confidence: 81%
“…It has been found that women with PCOS had a higher BMI than control women 13 , 18 . Other findings revealed that a proportion of women with menstrual disorders have significantly higher BMI (overweight and obese) than normal women 10 and the increase in BMI is associated with abnormality in menstrual cycle length, period duration, and blood loss 25 . Contrasting to this, malnutrition due to the eating disorder may often be associated with Oligo/Amenorrhea among adolescents and young women 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Body weight was measured with a digital scale of 0.1 kg calibrate with precision (Amgain et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%